25-Hydroxyvitamin D, Levels in Young Healthy Females Attending Isra University Hospital - Sadia Tabassum Abbasi, Shomail Siddiqui, Mumtaz Ali Qureshi, Mozna Talpur, Gulfareen Haider , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2016)
Objective: To determine 25-hydroxyvitamin D, (25-0H-D3) levels in young healthy female attending Isra University Hospital. Methods: This observational study was conducted in the departments of Biochemistry/Obstetrics and Gynecology, Isra University Hospital from June 2013 to December 2013. A sample of 90 females were selected according to pre-defined inclusion and exclusion criteria. Female of 18-28 years were selected through non-probability purposive sampling. Volunteers were asked to sign the consent for n. Vitamin D level was detected by the "ARCHITECT I 1000" system. Software SPSS 21.0 version was used for analysis. Numerical values were analyzed by one way ANOVA for differences among groups. Post Hoc Tukey-Cramer was used for differences between groups. Data was analyzed at 95% Confidence Interval (P< 0.05). Results: Age of study subjects was noted as 22.6+3.2 years. Mean (±SD) 25-0H-D, was noted as 26.20+4.30 ng/d1 (CI 24.90-27-49). Normal 25-0H-D, was noted in 4 (4.4%) of subjects. Insufficient and deficient 25-OH-D, were found in 6 (6.6%) and 80 (88.8')/0) of subjects respectively (p=0.0001). 25- OH-D, values of 8 ng/d1were noted. Conclusion: The present study reports severe deficiency of vitamin D, in female attending Isra University. Further studies are recommended to find prevalence of 25-OH-D]. Vitamin D supplementations may be prescribed.